Therapeutic Approach of Whole-Body Vibration Exercise on Wound Healing in Animal Models: A Systematic Review - Brites-Ferreira, Adrielli; Taiar, Redha; Cardoso, André Luiz Bandeira Dionizio; De Souza-Santos, Daysa; da Costa-Borges, Patricia Prado; Torres-Nunes, Luiza; Jaques-Albuquerque, Luelia Teles; Monteiro-Oliveira, Bruno Bessa; Boyer, Francois Constant; da Cunha Sá-Caputo, Danúbia; Rapin, Amandine; Bernardo-Filho, Mario (International Journal of Environmental Research and Public Health, 2023)
Human skin wounds pose a gathering threat to the public health, carrying an immense epidemiologic and financial burden. Pharmacological and non-pharmacological (NP) treatments have been proposed to the management of wound healing. Physical exercise is a strong NP intervention considered for patients in wound healing. Particularly, a type of exercise intervention known as whole-body vibration (WBV) exercise has gained increasing interest. WBV exercise is generated due to the transmission of mechanical vibrations, produced by a vibrating platform, to the body. The aim of this review was to summarize studies in experimental animal models using WBV exercise in wound healing. Searches were performed in EMBASE, PubMed, Scopus and Web of Science including publications on 21 November 2022 using the string “whole body vibration” AND “wound healing” (animal or mice or mouse or rat or rodent). The SYRCLE tool was used to assess the risk of bias (RoB). From 48 studies, five studies met the inclusion criteria. RoB indicated that none of the studies fulfilled all methodological analyzed criteria, resulting in possible biases. The studies were homogeneous, and results suggest beneficial effects of WBV exercise in wound healing, mainly related to enhancing angiogenesis, granulation tissue formation, reducing the blood glucose level and enhancing blood microcirculation, by increasing myofiber growth and rapid re-epithelialization. In conclusion, the various biological effects of the response to the WBV exercise indicate the relevance of this intervention in wound healing in animals. Moreover, considering the translation approach, it is possible to speculate that the beneficial effects of this non-pharmacological therapy might justify clinical trials for wound healing also in humans, after criterion evaluation.
Keywords: animal studies; healing; skin; vibration therapy; wound